A Case Report on Sacral Lipomyelomeningocele - Thambi, Smitha Sarah; Thomas, Angelin Grace; Saravanan, Kaushika (Indian Journal of Pharmacy Practice)
Lipomyelomeningocele (LMMC) is a neural tube defect characterized by the presence of a spinal lipoma that incorporates neural elements, leading to various symptoms like skin lesions, musculoskeletal issues, sensory deficits, and urinary dysfunction. It typically occurs in the lumbosacral region with a prevalence of 0.3-2.5 per 10,000 live births. A 1.4-year-old boy presented with a gradually enlarging swelling on the left lower back since birth, without any skin changes or discharge. Developmentally, he showed delays in mobility and increased urinary frequency compared to his sibling. Neurological examination revealed limb length discrepancy and absent anal wink reflex, suggesting potential tethered cord syndrome. Imaging confirmed a large subcutaneous lipoma with intradural extension at the S1-2 level. The patient underwent L5 to S3 laminectomy and subtotal excision of the lipoma. Postoperative management included dexamethasone and antibiotics. At discharge, he was afebrile, ambulant, and voiding normally, with stable neurological status. LMMC is a significant form of closed spinal dysraphism, often presenting with skin and musculoskeletal signs. Early surgical intervention is crucial for alleviating neurological deficits and preventing complications. This case underscores the importance of awareness and timely treatment in managing spinal dysraphism to optimize long-term outcomes.
Keywords: Lipomyelomeningocele; Case report; Neural tube defects; 1.4-year-old boy